2021
DOI: 10.1111/jfpp.15880
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma irradiation and pyrolysis on indigestible fraction, physicochemical properties, and molecular structure of rice starch

Abstract: Processing starch into resistant starch has many benefits for human health and the food industry. It has been demonstrated that resistant starch (RS) is not hydrolyzed by the amylase enzyme, so it is not absorbed through the small intestine. This has contributed to significantly reducing energy supply to the body without increasing blood sugar. Therefore, the RS has been considered as an essential nutrient to human, especially for obesity, diabetes, and cardiovascular diseases (Homayouni et al., 2013;Cao et al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Figure 2 shows the AAC of the irradiated cassava starches as a function of radiation dose. Similar to rice starch in our previous study, [21] gamma irradiation significantly reduced AAC of cassava starch. The apparent amylose of about 21.69% in initial cassava starch decreased to 21.09% by irradiation at 1 kGy, the decrease F I G U R E 1 Scanning electron microscopy (SEM) images of initial cassava starch (A), and the starches irradiated at 1 (B), 2.5 (C), 5 (D), 7.5 (E), and 10 kGy (F) is higher at higher dose, that is, to 17.63% in the starch irradiated at 10 kGy.…”
Section: Effect Of Irradiation On Morphology and Microscopic Structuresupporting
confidence: 85%
See 3 more Smart Citations
“…Figure 2 shows the AAC of the irradiated cassava starches as a function of radiation dose. Similar to rice starch in our previous study, [21] gamma irradiation significantly reduced AAC of cassava starch. The apparent amylose of about 21.69% in initial cassava starch decreased to 21.09% by irradiation at 1 kGy, the decrease F I G U R E 1 Scanning electron microscopy (SEM) images of initial cassava starch (A), and the starches irradiated at 1 (B), 2.5 (C), 5 (D), 7.5 (E), and 10 kGy (F) is higher at higher dose, that is, to 17.63% in the starch irradiated at 10 kGy.…”
Section: Effect Of Irradiation On Morphology and Microscopic Structuresupporting
confidence: 85%
“…However, the bands were not shifted to higher wavenumber as observed with rice starch as indicated in our previous study. [ 21 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Alcohols, including sugars, cause a hydrogen abstraction reaction by irradiation, which occurs at the carbon bearing hydroxyl group, and forms a hydroxylalkyl radical [27]. It has been reported that the main chain of polysaccharides, including cellulose or starches, is cleaved by ionizing radiation [28][29][30]. In the future, the physicochemical influence of additives by irradiation should be investigated, including disintegration tests for pills.…”
Section: Discussionmentioning
confidence: 99%